2000
DOI: 10.2214/ajr.174.6.1741723
|View full text |Cite
|
Sign up to set email alerts
|

Sonography of Morton's Neuromas

Abstract: Sonography can reveal a Morton's neuroma in 85% of cases. Identification of the presumed plantar digital nerve in continuity with the mass improves diagnostic confidence. The finding of an interdigital mass greater than 20 mm in length should raise suspicion of an abnormality other than a neuroma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
101
1
17

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 171 publications
(120 citation statements)
references
References 18 publications
1
101
1
17
Order By: Relevance
“…The differential diagnosis of MN must be made with stress fracture, tendon sheath ganglion, foreign body reaction, nerve sheath tumor, dislocation of the metatarsophalangeal joint and intermetatarsal bursitis [15]. Diagnosis of MN is usually made through an accurate anamnesis and physical examination and must be confirmed by US [9].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The differential diagnosis of MN must be made with stress fracture, tendon sheath ganglion, foreign body reaction, nerve sheath tumor, dislocation of the metatarsophalangeal joint and intermetatarsal bursitis [15]. Diagnosis of MN is usually made through an accurate anamnesis and physical examination and must be confirmed by US [9].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies identified 95-98% of MNs prospectively and up to 100% retrospectively [9]. Neuromas have a US appearance of a hypoechoic mass, with regard to the muscle.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations